2017
DOI: 10.1038/s41467-017-01987-2
|View full text |Cite
|
Sign up to set email alerts
|

Break-induced replication promotes formation of lethal joint molecules dissolved by Srs2

Abstract: Break-induced replication (BIR) is a DNA double-strand break repair pathway that leads to genomic instabilities similar to those observed in cancer. BIR proceeds by a migrating bubble where asynchrony between leading and lagging strand synthesis leads to accumulation of long single-stranded DNA (ssDNA). It remains unknown how this ssDNA is prevented from unscheduled pairing with the template, which can lead to genomic instability. Here, we propose that uncontrolled Rad51 binding to this ssDNA promotes formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
61
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(75 citation statements)
references
References 66 publications
(87 reference statements)
3
61
0
Order By: Relevance
“…Dmc1 Prevents Heteroduplex Joint Disruption by Srs2. Srs2 has the ability to disrupt heteroduplex DNA intermediates, and this activity plays a central role in the ability of Srs2 to contribute to genome integrity (13,15,18,19,27). Similarly, we have shown that Srs2 can disrupt short heteroduplex DNA joints made with Rad51-ssDNA and 70-bp dsDNA fragments harboring a 15-nt tract of homology complementary to the presynaptic ssDNA (44).…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…Dmc1 Prevents Heteroduplex Joint Disruption by Srs2. Srs2 has the ability to disrupt heteroduplex DNA intermediates, and this activity plays a central role in the ability of Srs2 to contribute to genome integrity (13,15,18,19,27). Similarly, we have shown that Srs2 can disrupt short heteroduplex DNA joints made with Rad51-ssDNA and 70-bp dsDNA fragments harboring a 15-nt tract of homology complementary to the presynaptic ssDNA (44).…”
Section: Resultsmentioning
confidence: 77%
“…1A) (2, [10][11][12][13][14][15][16]. Consequently, srs2Δ mutants have a mitotic hyperrecombination phenotype characterized by frequent crossovers and gross chromosomal rearrangements (15,16,(18)(19)(20). Srs2 antirecombinase activity is counterbalanced by the Rad51 paralog complex Rad55/57, the Shu complex (composed of the Rad51 paralogs Psy3 and Csm2 and the SWIM-domain proteins Shu1 and Shu2), and Rad52, all of which enhance assembly or stability of early HR intermediates ( Fig.…”
mentioning
confidence: 99%
“…In consequence, elimination of Srs2 leads to an increase of crossover products (Ira, Malkova et al, 2003, Mitchel, Lehner et al, 2013, Robert, Dervins et al, 2006. Thus besides Mph1, Srs2 may also suppresses BIR, however we have not tested Srs2 here because it is itself very important for BIR (Elango, Sheng et al, 2017). Lack of the enzymes regulating BIR frequency is partially (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In wild-type cells, Srs2 seems to remove Rad51 assembly from the intermediates for the second end capture. Importantly, genetic analysis of mitotic recombination in the srs2 mutant suggest the role of Srs2 to facilitate the annealing of the newly synthesized strand to second resected ends by removing Rad51 from the second end (Elango et al 2017; Ira et al 2003; Liu et al 2017; Mitchel et al 2013).…”
Section: Discussionmentioning
confidence: 99%